Oral and written communication skills of adolescents in youth justice with and without prenatal alcohol exposure - Kippin, Natalie Ruth (Curtin University, 2021)
This research investigated the communication skills of adolescents in youth detention in Western Australia (WA), a context in which fetal alcohol spectrum disorder (FASD) is highly prevalent and Aboriginal young peoples are over-represented. Many adolescents were multilingual, reflecting linguistic strengths. Oral and written language difficulties were common. A high prevalence of language disorder (LD), including LD associated with FASD was identified. Speech anomalies were also identified. Speech-language-pathology services are required in youth justice in WA.